Research on learning and teaching of languages other than English in System. (August 2021) - Guo, Quanjiang; Zhou, Xiaozhou (Emily); Gao, Xuesong (Andy)
Abstract: In this review of System 's scholarship on the learning and teaching of languages other than English (LOTEs), we focus on 12 articles on language pedagogy and language learners, selected from a total of 208 relevant articles published in the journal (until 2020). The review affirms the journal's commitment to the dissemination of scholarship for language teachers to address 'all languages'. It identifies the evolving research trajectory targeting language learners and their language development through increasingly sophisticated methodologies. These have helped to generate deeper insights into the role of language learner characteristics in language learning. Articles on language pedagogy, which are closely associated with studies on language learners and their language development, have addressed a variety of topics, such as reading, pronunciation, task motivation and engagement, story retelling, group cohesion, and classroom management. We conclude the review with our thoughts on which research areas could be more fully represented within the journal in order to fulfil its mission statement.